Rates of cortical thinning in Alzheimer's disease signature regions: pathological influences and cognitive consequences in members of the 1946 British birth cohort. (20th December 2022) - Keuss, Sarah E; Cash, David M; Nicholas, Jennifer M; Parker, Thomas D; Lane, Christopher A; Keshavan, Ashvini; Buchanan, Sarah M; Wagen, Aaron Z; Storey, Mathew; Harris, Matthew J; Lu, Kirsty; James, Sarah‐Naomi; et al.
Abstract: Background: Consistent patterns of reduced cortical thickness (so‐called signature regions) have been identified in early Alzheimer's disease (AD), including in the pre‐dementia stages, but studies investigating the pathological underpinnings and cognitive consequences of longitudinal changes in these regions have been limited. Method: 337 cognitively normal participants (mean [SD] age 70.5 [0.6] years) underwent 18F‐florbetapir amyloid‐ß PET, volumetric MRI, and cognitive assessment as part of Insight 46, a sub‐study of the 1946 British birth cohort (Table 1 for characteristics). Baseline and follow‐up T1‐weighted MRI (mean [SD] interval 2.4 [0.2] years) were processed using Freesurfer's longitudinal stream (v.7.1.0) and cortical thickness was derived in two AD signatures (Table 2 footnote for details). Linear regression was used to test whether rates of change in AD signature cortical thickness were influenced by baseline amyloid‐ß deposition (positive/negative status or continuous SUVR) or white matter hyperintensity volume (WMHV; a marker of presumed cerebrovascular disease), and whether they were related to longitudinal cognitive change as measured using the Preclinical Alzheimer Cognitive Composite (PACC). Covariates included sex, age at baseline scan, childhood cognition, educational attainment, and socioeconomic position. Interaction terms were added to test whether associations with longitudinal cognitive change differed by baseline amyloid‐ß status. Result: Higher baseline WMHV was associated with faster rates of cortical thinning in AD signature regions, but baseline amyloid‐ß status and SUVR were not (Table 2; Figure 1). There were differential effects of rates of change in AD signature cortical thickness by baseline amyloid‐ß status, whereby greater rates of AD signature cortical thinning predicted faster rates of PACC decline in amyloid‐ß positive participants only (Table 3; Figure 2). Conclusion: Cortical thinning in AD signature regions may arise via non‐amyloid‐ß pathways in cognitively normal elderly. However, the presence of amyloid‐ß may make individuals more susceptible to the effects of faster rates of cortical thinning in these regions (or vice versa) since these factors interact to influence rates of cognitive decline. These findings provide insight into processes that might underlie progression to dementia in later life and have implications for the utility of AD signature cortical thickness as a biomarker in the preclinical phase of AD.